Effectiveness of Instruction Program on Teachers’ Performance toward Counseling for Primary School Pupils with Attention Deficit and Hyperactivity Disorder - Ali Abed Kadhim; Alkhazrajy, Lujain Anwar (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): the study aims to evaluate teachers’ performance of counselling for primary school pupils with ADHA; to determine the effectiveness of the program on teachers’ performance of counselling, and to identify the relationship between teachers’ performance and their demographic characteristics of age, gender, education levels and years of employment. Methodology: A quasi-experimental (pre-posttest) design was carried out at Al-Firdous mixed primary School The study was started from March 28th 2022 to April 24th 2023. The sample was non-probability (purposive sample) of (60) teachers. The data were collected before and after the application of the program by direct interview using constructed questionnaire. Instruction program is designed on the basis on the results of teachers’ need assessment, and from review of the relative scientific literature and previous studies. A panel of (10) experts to determine the content validity of an early-stage instrument. Cronbach alpha is used to determine the questionnaire’s reliability; a correlation coefficient is calculated (0.908). Data were collected through the utilization of the study instruments and the application of the interview and self-report technique. Version (SPSS) of the software program was used to examine the data (25). Results: Analysis of the study data indicates The effectiveness of the instruction program is reflected at all three time periods, the performance of teachers on the pretest was poor, but improved significantly on the posttest I and posttest II. There are significant variations between pre and posttest I and posttest II of the research sample (P = 0.001), indicating a high degree of significance, these demonstrate the effectiveness of the educational program. It was found that there are differences between the study group and the control group, which show that the relationship between teachers’ performance and demographic characteristics shows a high statistically significant relationship between teachers’ performance and (age, years of employment) variables. Conclusions: The findings of the study demonstrated considerable effectiveness of the instruction program on teachers’ performance for providing counseling to pupils with attention deficit hyperactivity disorder. Some demographic characteristics, such as teachers’ ages and Years of employment, exhibited a substantial positive link with their post-assessment performance. Recommendations: The program can be utilized as an effective tool to improve these teachers’ performance about attention deficit and hyperactivity disorder nation-wide. Further research can be conducted on large sample size with different characteristics.